2024
DOI: 10.3390/ani14030364
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Caustic Soda and Benzocaine on Directed Grooming to the Eyestalk in the Glass Prawn, Palaemon elegans, Are Consistent with the Idea of Pain in Decapods

Stuart Barr,
Robert W. Elwood

Abstract: Acceptance of the possibility of pain in animals usually requires that various criteria are fulfilled. One such criterion is that a noxious stimulus or wound would elicit directed rubbing or grooming at the site of the stimulus. There is also an expectation that local anaesthetics would reduce these responses to damage. These expectations have been fulfilled in decapod crustaceans but there has been criticism of a lack of replication. Here, we report an experiment on the effects of a noxious chemical, sodium h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…It was also like a study on the shore crab, H. sanguineus , in which claw-bearing limbs were injected with formalin, and shaking, rubbing and unusual postures of that limb occurred [ 9 ]. These studies have demonstrated that both acetic acid and formalin causes decapods to show distinct activities that are consistent with the idea of pain, and similar effects have been noted with caustic soda brushed onto an eye in glass prawns [ 8 ].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It was also like a study on the shore crab, H. sanguineus , in which claw-bearing limbs were injected with formalin, and shaking, rubbing and unusual postures of that limb occurred [ 9 ]. These studies have demonstrated that both acetic acid and formalin causes decapods to show distinct activities that are consistent with the idea of pain, and similar effects have been noted with caustic soda brushed onto an eye in glass prawns [ 8 ].…”
Section: Discussionmentioning
confidence: 63%
“…Morphine has analgesic effects in vertebrates [ 1 , 2 , 3 ], but the evidence for such effects in crustaceans is weak or lacking [ 35 ]. However, local anaesthetics, such as benzocaine, are effective in reducing responses to noxious stimuli in decapods [ 5 , 8 ]. Benzocaine blocks the transmission of action potentials along axons, whereas opiates block transmission across synapses by inhibiting specific neurotransmitters [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is like a previous study that seemed to show some hesitation to enter a shelter in which a shock was delivered [ 20 ], but, as with that previous study, we cannot exclude the possibility that a shock toward the fifth leg reduces the ability to walk. We note, however, that noxious chemicals applied to the eyes or antennae of two species of prawns also increased the latency in the initiation of walking [ 25 , 26 ], and this is unlikely to be caused by reduced walking ability. We also examined contact with the walls of the arena as a percentage of the time the crabs were in the arena.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the present observations, and those of numerous other experiments, add to the idea of pain in decapods. For example, we saw a directed rubbing of the site of noxious stimulus application [ 25 , 30 , 31 , 32 ], swift avoidance learning [ 17 , 33 ], long-term changes in behaviour [ 13 , 31 ], anxiety [ 18 , 34 ], giving up vital resources to escape [ 20 ], physiological changes [ 18 , 34 , 35 , 36 ], in addition to trade-offs noted above. With the increasing number of studies that provide data consistent with expectations of pain, there was an increasing acceptance that pain is possible or even likely.…”
Section: Discussionmentioning
confidence: 99%